Loss of pesticides from a litchi orchard to an adjacent stream in northern Thailand - Kahl G. (2014)
In the hill country of northern Thailand use of agrochemicals is increasing steadily and contaminating streams and groundwater. We have measured pesticide leached from a litchi orchard to an adjacent stream and identified the flow components contributing to the pesticide transport after installing two discharge measurement stations with automatic water samplers in the stream. For 2 years, between June and September, we applied methomyl, and in 1 year additionally chlorothalonil, to the 2-ha orchard and monitored water fluxes and pesticide concentrations in the stream water. Pesticide loads ranged from 1.6 to 3% of mass applied for chlorothalonil, a strongly sorbing fungicide, and 6.4-11.4% for the more weakly sorbing insecticide methomyl. Directly after application, pesticide transport was dominated by a fast flow component, reaching the flume before the discharge peak. Later, pesticides were transported mainly by preferential interflow, which peaked about 30 hours after a rain event. The groundwater pathway was not found to contribute to pesticide loss. Antecedent rain conditions proved to be important for the pesticide transport behaviour. While at the beginning of the rainy season large falls of rain did not lead to pesticide contamination, at the end of the season pesticide transport was induced by as little as 0.1 mm of rain. The occurrence of preferential interflow means that the hilly regions in northern Thailand are highly susceptible to contamination by pesticides used by farmers. © 2007 British Society of Soil Science.